2016
DOI: 10.1007/s00213-016-4238-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic effects of tobacco smoke constituents in nonhuman primates

Abstract: Selected minor tobacco alkaloids have nicotinic-like effects that may contribute to tobacco consumption and addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…(1)-Epibatidine Discrimination Consistent with our previous observations (Desai and Bergman, 2015;Desai et al, 2016a), reliable discriminativestimulus control by 0.001 mg/kg (1)-epibatidine was maintained in all four subjects throughout the present study (Fig. 3, top panel).…”
Section: Food-reinforced Behaviorsupporting
confidence: 91%
See 3 more Smart Citations
“…(1)-Epibatidine Discrimination Consistent with our previous observations (Desai and Bergman, 2015;Desai et al, 2016a), reliable discriminativestimulus control by 0.001 mg/kg (1)-epibatidine was maintained in all four subjects throughout the present study (Fig. 3, top panel).…”
Section: Food-reinforced Behaviorsupporting
confidence: 91%
“…The nAChR partial agonist, lobeline, did not generalize for (1)-epibatidine (8% 6 5%). The effects of higher doses of each of these nicotinic partial agonists were not determined because in the present or previous studies 0.25 or 0.5 log-unit higher doses either markedly disrupted responding or produced untoward effects in squirrel monkeys (Desai and Bergman, 2014;Desai et al, 2016a). Based on the mean ED 50 values, the rank order of potency of drugs that produced epibatidine-like effects was (1)-epibatidine (2)-epibatidine .…”
Section: Food-reinforced Behaviormentioning
confidence: 87%
See 2 more Smart Citations
“…Racemic anatabine was marketed as an herbal supplement called Anatabloc by Rock Creek Pharmaceuticals. Several studies supported by this company have shown that anatabine, in addition to its anti-inflammatory actions, has procognitive [40][41][42][43], neuro-protective [44], immune disease modulating [45,46], and smoking cessation actions. Anatabine partially substitutes for nicotine in drug discrimination behavioral assays but does not have the addictive potency of nicotine [47,48].…”
Section: Discussionmentioning
confidence: 99%